Teores de nutrientes, valores energéticos e legalidade em bebidas não alcoólicas comerciais de manga e de goiaba - Nogueira, Andressa Milene Parente; Venturini Filho, Waldemar Gastoni [UNESP] (EIA Energy in Agriculture, 2013)
The objective of this research was to compare nutrients contents (carbohydrates, protein, and total fat) and energy values informed on the labels of commercial mango and guava non-alcoholic beverages with results found in laboratory tests and the standards established by Brazilian legislation. Among the mango beverages, four trademarks of unsweetened tropical juices, three sweetened, six conventional nectars, and three light were analyzed. Four guava unsweetened tropical juices, three sweetened, five conventional nectars, and three light were also analyzed. The carbohydrate, protein, and total fat contents were obtained by chemical analysis of these beverages, while their energy values were estimated by centesimal calculating, using conversion factors for carbohydrates (4kcal/g), protein (4kcal/g), and total fat (9kcal/g). The beverages that nutrients contents and energy values obtained in the laboratory exceeded the tolerance of ± 20%, calculated from data informed in their packaging, were considered outside of quality standards. Of the sixteen commercial mango beverages analyzed, half had the nutrients contents and energy values together correctly declared on their labels. Of the fifteen of guava beverages, only five could be considered within the quality standards.

O objetivo deste trabalho foi comparar os teores de nutrientes (carboidratos, proteínas e gorduras totais) e valores energéticos informados nos rótulos de bebidas não-alcoólicas comerciais de manga e de goiaba com os resultados encontrados em análises laboratoriais e padrões estabelecidos pela legislação brasileira. Dentre as bebidas de manga, foram analisadas quatro marcas de sucos tropicais não adoçados, três adoçados, seis néctares convencionais e três light. Dentre as de goiaba, quatro sucos tropicais não adoçados, três adoçados, cinco néctares convencionais e três light. Os teores de carboidratos, proteínas e gorduras totais foram obtidos através de análise química dessas bebidas, enquanto que os seus valores energéticos foram estimados através de cálculo centesimal, utilizando fatores de conversão para carboidratos (4kcal/g), proteínas (4kcal/g) e gorduras totais (9kcal/g). As bebidas cujos teores de nutrientes e valores energéticos obtidos em laboratório excederam o intervalo de tolerância de ± 20%, calculado a partir dos dados declarados em suas embalagens, foram consideradas fora dos padrões de qualidade. Das dezesseis bebidas comerciais de manga analisadas, metade declarou os teores de nutrientes e valores energéticos, em conjunto, de maneira correta em seus rótulos. Enquanto que, das quinze de goiaba, cinco puderam ser consideradas dentro dos padrões de qualidade.
Nutrients contents, energy values, and legality of the mango and guava nonalcoholic beverades commercial
Keywords: Mangifera indica; Psidium guajava; Labeling; Mangifera indica; Psidium guajava; Rotulagem